2023
DOI: 10.3390/cancers15041181
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Magnetic Resonance Imaging-Targeted versus Systematic Prostate Biopsy; Systematic Review and Meta-Analysis

Abstract: Introduction: Robot-assisted devices have been recently developed for use in prostate biopsy. However, it is possible advantages over standard biopsy remain unclear. We aimed to assess the diagnostic performance and safety of robot-assisted targeted (RA-TB) and systematic prostate biopsies (RA-SB). Methods: A systematic literature search was performed in MEDLINE and Scopus databases. The detailed search strategy is available at Prospero (CRD42021269290). The primary outcome was the clinically significant prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Petov et al have recently published a meta-analysis which concluded that robotic biopsy on targeted and systematic biopsy have comparable csPCa and overall detection rates [ 58 ]. In line with the results of these studies, the Cochrane systematic review makes clear its position regarding the complementarity of systematic biopsies with targeted biopsies via the transrectal route [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Petov et al have recently published a meta-analysis which concluded that robotic biopsy on targeted and systematic biopsy have comparable csPCa and overall detection rates [ 58 ]. In line with the results of these studies, the Cochrane systematic review makes clear its position regarding the complementarity of systematic biopsies with targeted biopsies via the transrectal route [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The only study where saFB was superior to cFB is the one by Patel et al [ 20 ], in which the software-assisted fusion was performed with an elastic semi-automatic robot-assisted technique (UroBiopsyTM; Biobot Surgical). Their results may be in line with the inherent features of the robotic system, which allows for the reduction in prostate displacement and deformation during the biopsy, thus minimizing the mismatches of the fusion-guided process leading to more precise punctures and representing a promising tool to develop in the near future [ 39 ].…”
Section: Discussionmentioning
confidence: 86%
“…Regarding the complementarity of systematic biopsies for detecting csPCa, Petov et al ( 40 ) have published a meta-analysis concluding that targeted and systematic biopsies have comparable csPCa detection rates. Marra et al ( 41 ) reported that the PCa detection rate of targeted biopsy was higher than that of systematic biopsies, but their role should not be overlooked, and the combination of targeted and systematic biopsies is essential.…”
Section: Discussionmentioning
confidence: 99%